Vascular Function at Baseline in the Hemodialysis Fistula Maturation Study. Issue 7 (July 2016) - Dember, Laura M.; Imrey, Peter B.; Duess, Mai‐Ann; Hamburg, Naomi M.; Larive, Brett; Radeva, Milena; Himmelfarb, Jonathan; Kraiss, Larry W.; Kusek, John W.; Roy‐Chaudhury, Prabir; Terry, Christi M.; Vazquez, Miguel A.; et al.
Abstract : Background: End‐stage renal disease is accompanied by functional and structural vascular abnormalities. The objective of this study was to characterize vascular function in a large cohort of patients with end‐stage renal disease, using noninvasive physiological measurements, and to correlate function with demographic and clinical factors. Methods and Results: We analyzed cross‐sectional baseline data from the Hemodialysis Fistula Maturation Study, a multicenter prospective observational cohort study of 602 patients with end‐stage renal disease from 7 centers. Brachial artery flow‐ and nitroglycerin‐mediated dilation, carotid‐femoral and ‐radial pulse wave velocity, and venous occlusion plethysmography were performed prior to arteriovenous fistula creation. Relationships of these vascular function measures with demographic, clinical, and laboratory factors were evaluated using linear mixed‐effects models. Arterial function, as assessed by flow‐ and nitroglycerin‐mediated dilation and carotid‐femoral pulse wave velocity, worsened with increasing age and diabetes mellitus. Venous capacitance decreased with diabetes mellitus but not with age. Flow‐mediated dilation was higher among patients undergoing maintenance dialysis than for those at predialysis, and a U‐shaped relationship between serum phosphorus concentration and flow‐mediated dilation was evident. Partial correlations among different measures of vascular function, adjusting for demographic factors, diabetes mellitus, and clinical center, were modest or essentially nonexistent. Conclusions: Multiple demographic and clinical factors were associated with the functions of vessels of different sizes and types in this large cohort of patients with end‐stage renal disease. Low correlations between the different measures, controlling for demographic factors, diabetes mellitus, and center, indicated that these different types of vascular function otherwise vary heterogeneously across patients.